Automation with RPA (Robotic Process Automation) - Ghosh, G (International Journal of Computer Sciences and Engineering, 2025)
We’re in the midst of a digital revolution in which technology is moving forward at exponential speed. Robotic Process Automation and Artificial intelligence is gaining in acquisition. Robotic process automation is a key component of the digital revolution, driving much of the long-tail process automation that were previously impossible to achieve. Robotics is a field of engineering that deal with design and application of robots and the use of computer for their manipulation and processing. Robots are used in industries for speeding up the manufacturing process. Automation and Robotics Engineering is the use of control systems and information technologies to reduce the need for human work in the production of goods and services. The Robotic process automation technology is based on perception of software robot. RPA can be used to automate workflow, infrastructure, back office process which are labor intensive. Basically involving RPA has eliminated lots of manual effort which helps business to keep pace with current technology trends. In this paper I will explain how Robotic automation process will help to save manual exertion and time